2016
DOI: 10.1016/j.dental.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biofilm formation on the optical properties of novel bioactive glass-containing composites

Abstract: Objective Bioactive glass (BAG) has been suggested as a possible additive for dental restorative materials because of its antimicrobial effect and potential for promoting apatite formation in body fluids. The purpose of this study was to investigate the effects of bacterial biofilm on the change of colorimetric value and translucency of novel BAG-containing composites having different initial surface roughness. Methods Composites with 72 wt% total filler load were prepared by replacing 15% of the silanized S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…When the composite groups were compared, the BAG group showed the greatest color change after immersion for 1, 7, and 30 days. Similar to our findings, Hyun et al reported that color changes were higher in a BAG group as compared with those in a BAG‐Flor group . Previous research showed that BAG released calcium ions during dissolution, which elevated the pH of interfacial solutions and prevented the attachment and growth of microorganisms .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…When the composite groups were compared, the BAG group showed the greatest color change after immersion for 1, 7, and 30 days. Similar to our findings, Hyun et al reported that color changes were higher in a BAG group as compared with those in a BAG‐Flor group . Previous research showed that BAG released calcium ions during dissolution, which elevated the pH of interfacial solutions and prevented the attachment and growth of microorganisms .…”
Section: Discussionsupporting
confidence: 57%
“…Similar to our findings, Hyun et al reported that color changes were higher in a BAG group as compared with those in a BAG-Flor group. 29 Previous research showed that BAG released calcium ions during dissolution, which elevated the pH of interfacial solutions and prevented the attachment and growth of microorganisms. 30 Other research demonstrated that the acid produced by bacteria can cause superficial hydrolysis and degradation, possibly followed by slight penetration by staining agents and reactions with the superficial layer of composites.…”
Section: Discussionmentioning
confidence: 99%
“…BAG Among bioceramics, BAG is a relatively new material which has been incorporated into dental resin composites and adhesives. A total 20 studies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] was found as per the inclusion criteria, whereby seven studies 92,[94][95][96]98,106,108) were based on fluoride-based bioactive glass (F-BAG). Few studies showed doping of zinc 101,102,107) , silver 110) , and niobiophosphate 109) in BAG powders.…”
Section: Acpmentioning
confidence: 99%
“… 10 The translucency of dental restorations is also influenced by the type of dental materials. 13 14 15 16 17 18 19 20 Thus, the translucency of ceramics and composites is widely reported in the literature. It has been demonstrated that the translucency parameters of ceramic materials are better than composites.…”
Section: Introductionmentioning
confidence: 99%